2016
DOI: 10.1590/1806-9061-2016-0263
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Growth Curves of Turkeys Reared in Different Breeding Systems (Intensive and Free-Range) with some Nonlinear Models

Abstract: KeywordsBreeding system, growth models, large white turkey, live weight. ABSTRACTThe objective of this study was to identify the growth curve of live weight of turkeys reared in different systems (intensive and free-range) with the best mathematical model. To achieve this goal, the live weight of male and female turkeys (Large White) reared for 0-18 weeks were used. Logistic, Gompertz, Von Bertalanffy, and Gauss were used to determine the best model for the turkeys. In comparison of the models, values of Coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Results described in Table 1 clearly postulated significantly higher body weight in black colour male turkey even in first week of rearing compared to female turkey, suggesting that one can identify male or female poults even after 7 days of rearing by the observation of their body weight differences. In a recent published report by Sogut et al (2016), it was shown that male poults hatching weight (63.10g/poult) was significantly higher than that of the female (61.87g/poult). Further, they mentioned the significant differences in body weight at 2 nd week (male = 234.71g/bird, female = 224.75g/bird) and 4 th week (male = 687.14g/bird, female = 642.40g/bird) of age.…”
Section: Resultsmentioning
confidence: 94%
“…Results described in Table 1 clearly postulated significantly higher body weight in black colour male turkey even in first week of rearing compared to female turkey, suggesting that one can identify male or female poults even after 7 days of rearing by the observation of their body weight differences. In a recent published report by Sogut et al (2016), it was shown that male poults hatching weight (63.10g/poult) was significantly higher than that of the female (61.87g/poult). Further, they mentioned the significant differences in body weight at 2 nd week (male = 234.71g/bird, female = 224.75g/bird) and 4 th week (male = 687.14g/bird, female = 642.40g/bird) of age.…”
Section: Resultsmentioning
confidence: 94%
“…Growth curves have been developed to compare species ( Anthony et al., 1991 ; Knížetová et al., 1995 ), where it was concluded that selection age for BW compared to their mature weight is critical. In turkey production, the Von Bertalanffy model was used to high coefficient of determination ( R 2 ) and Mean Square Error ( MSE ) when developing growth curves in different breeding systems ( Sogut et al., 2016 ). These grow curves are essential to determine feed requirements and live weight ( ŞENGÜL and Kiraz, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bearing in mind that the primary objective of the paper was to contribute to the understanding of the global trade network in the context of transboundary spread of poultry diseases, and recognizing that the risk of disease spread associated with poultry differs depending on their age, analyses were performed separately for 3 networks: 1) the network of live poultry lighter than 185 g; 2) the network of live poultry of 185 g or more; and 3) the network of poultry hatching eggs ( Boyle et al., 2000 ; Ellis et al., 2005 ; McQuiston et al., 2005 ; Shankar, 2008 ). Network 1 is for chicken aged from 1 d to approximatively 3 wk, ducks and turkeys aged from 1 d to approximatively 1 wk, and guinea fowls aged from 1 d to approximatively 2 wk ( Aggrey, 2002 ; Nahashon et al., 2006 ; Osei-Amponsah et al., 2014 ; Chang et al., 2016 ; Sogut et al., 2016 ). Network 2 is for poultry older than that age.…”
Section: Methodsmentioning
confidence: 99%